Rock Physics Characterization using Physical Methods on Powders - Ahmed, Zubair (Curtin University, 2018)
This study describes a detailed investigation of quantifying key micro-structural parameters of the unconsolidated granular media and their relationship with the grain shape factors calculated from micro-CT images. These parameters are combined with the contact based effective medium models to calculate the elastic properties of the constituent grains after utilising stress dependent ultrasonic velocities of the samples. Thus developed techniques produce good results for mono-mineral quartz sands and one of the poly-mineral rock powder.